PENGARUH WORK FAMILY CONFLICT TERHADAP TURNOVER INTENTION MELALUI MEDIASI KEPUASAN KERJA PADA HOTEL GRAND INNA KUTA - Wulandari, Ida Ayu Diah; Adnyani, I Gusti Ayu Dewi (E-Jurnal Manajemen; Vol 5 No 10 (2016), 2016)
Work family conflict is one of the problems that must be faced by employees. This conflict occurs because the working hours and workload which is owned by an employee is too dense, so that all the attention and mind too tercurahkan on one role only. The existence of this conflict can also affect the job satisfaction of employees, which in turn leads to the employee turnover intention. This research was conducted at the Grand Inna Kuta. The number of respondents who were taken as many as 77 employees woman, with a census or sampling methods saturated. Data collected through questionnaires using Likert scale. The analysis technique used is path analysis. Based on the results of research conducted found that work family conflict negatively affects job satisfaction. Work family conflict positive effect on turnover intention. Job satisfaction negatively affect turnover intention. Work family conflict negatively affects turnover intention through job satisfaction.
Keywords: Work Family Conflict, Job Satisfaction, Turnover Intention